The temporal dynamics of enhancing a human declarative memory during reconsolidation - Coccoz, Veronica (2013)
When a consolidated memory is reactivated, it can become labile and prone to enhancement or disruption, a process known as reconsolidation. The reconsolidation hypothesis has challenged the traditional view that memories after consolidation are fixed and unchangeable. Recent studies suggest that the mechanisms mediating memory retrieval and the mechanisms that underlie the behavioral expression of memory can be dissociated, offering a new promise for the understanding of human memory persistence. Although reconsolidation studies typically use amnesic agents, it has also been shown that memory can be enhanced by pharmacological agents and real-life events during reconsolidation. Recently, we demonstrated that a mild stressor, cold pressor stress (CPS), can enhance human declarative memory during reconsolidation in a cued-recall test. Here we evaluate whether the recollection of 7- or 20-day-old long-term memories can be improved by exposure to two different neuromodulators: a mild stressor and glucose during reconsolidation. As expected, poor and very poor memory performance was found at the time of memory reactivation (days 6 and 20 after training). CPS during reconsolidation improved the long-term expression of a declarative memory 6 -but not 20-days after training. However, the administration of an oral source of glucose (juice), but not a diet juice, can enhance memory during reconsolidation even 20. days after training. Interestingly, when a recognition test was applied instead of a cued-recall test, memory performance was still robust at both 1 and 3. weeks after training. Here we show that the period in which this memory can be reactivated and become labile largely exceeds the period in which that memory is recalled, proving evidence that conscious access is not needed for reconsolidation. Present results are consistent with dissociation between the mechanisms mediating memory labilization and the mechanisms that underlie the behavioral expression of memory.